Approaching the Nernst Detection Limit in an Electrolyte-Gated Metal Oxide Transistor - Lee, Seyeong; Park, Sungjun; Kim, Chang Hyun; Yoon, Myung Han (IEEE Electron Device Letters, 2021)
In this letter, we demonstrate direct high-sensitivity proton detection by novel electrolyte-gated thin-film transistors. Integrating a sol-gel derived oxide channel and liquid electrolytes, a current switching by a factor of 107 was achieved within a 0.5 V gate window. Manipulation of the ionic strength in the gating solution led to an impressively large electrostatic shift (48 mV/pH), outperforming reported devices and ultimately approaching the Nernst limit. By means of impedance spectroscopy and transient measurements, we identified spatial compression of ionic charges at the electrical double layers as the origin of sensitivity, with the response time being dominated by the ion-transport resistance.
Keywords: Current switching; Electrical double layers; Impedance spectroscopy; Liquid electrolytes; Novel electrolytes; Proton detections; Spatial compression; Transient measurement; electrolyte-gated thin-film transistors; impedance spectroscopy; Metal oxide semiconductors; pH sensing